The Effect of Selling Price, Production Costs, Land Area, and Credit Access on Horticultural Farmers' Income in East Java: Pengaruh Harga Jual, Biaya Produksi, Luas Lahan, dan Akses Kredit terhadap Pendapatan Petani Hortikultura di Jawa Timur - Dwi Laila Maulida; Andrean Eka Hardana; Ajik Siswantoro (Jurnal Ilmiah Manajemen Agribisnis, 2026)
This study aimed to analyze the socio-economic factors affecting the income of horticultural farmers in East Java. The independent variables included selling price, production costs, land area, and credit access. Data were collected from two horticultural centers, namely Wonomulyo Village (Malang Regency) and Ngadirejo Village (Pasuruan Regency), with 160 farmers selected purposively as respondents. Data were gathered through interviews using questionnaires and analyzed using multiple linear regression. The results showed an adjusted R² value of 0.849, meaning that the four independent variables explained 84.9% of the dependent variable (income), while the remaining 15.1% was explained by other variables outside the model. Among the four variables, land area had a significant and positive effect on income. The regression coefficient for land area was 4.317, indicating that the larger the cultivated land, the higher the horticultural farming income in East Java. Thus, increasing farmers' income is largely determined by land area, in addition to selling price, production costs, and credit access, which also contribute simultaneously.